Les mouvements sociaux en Martinique dans les années 1960 et la réaction des pouvoirs publics - Laurent Jalabert (Études Caribéennes)
Social conflict in the West Indies in 2009 was highly publicized in France where it seemed exceptional, as a first event in the social field likely to shake the authority of a government previously inflexible in this area. In view of the historian, social conflict Caribbean has nothing new. He slips into a West Indian social history of the movement which is still a field little studied by the more contemporary history. A quick look back at two major social conflicts in 1959 and 1961 can relocate the impact of the social instincts of the French policy for overseas. The eye of the historian here has brought nuance to the "exceptional" at the time and recalls that out of the crisis in 2009 found strangely reminiscent of those used half a century ago!